A Study of the Relationship Between Teachers’ Perception Towards Director’s Transformational Leadership Style and Knowledge Management at the New Zealand College of Higher Education - Cai, Qian; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2021)
The purpose of this study was to examine the relationship between the teachers’ perception of the director’s transformational leadership style and knowledge management at the New Zealand College of Higher Education. This study had three objectives, which were: (1) to identify the teachers’ perception towards director’s transformational leadership style at the New Zealand College of Higher Education (2) to identify the teachers’ perception towards knowledge management at the New Zealand College of Higher Education, and (3) to determine the relationship between teachers’ perception towards director’s transformational leadership style and knowledge management at the New Zealand College of Higher Education. The study included 96 participants, and they were all teachers at the New Zealand College of Higher Education during the academic year of 2020. The researcher conducted a quantitative study to measure the research objectives and to test the research hypothesis. Then researcher used a statistical software program to analyze the collected data. Finally, this study found a significant relationship between the teachers’ perception of the director’s transformational leadership style and knowledge management at the New Zealand College of Higher Education.